Peningkatan Pembelajaran Bahasa: Penggunaan Teknik Shadowing dengan Google Translate Untuk Meningkatkan Pengucapan Siswa di Sekolah Menengah - Maqbulin, Arjunina (Balai Diklat Keagamaan Surabaya, 2025)
In teaching English, pronunciation is crucial as it plays a significant role in effective communication. Despite its importance, many students struggle with pronunciation. The aim of this research is to investigate the effectiveness of using the shadowing technique with Google translate to improve students’ Pronunciation. This highlights the necessity of employing appropriate methods for teaching pronunciation. One effective technique is the shadowing method using Google Translate. The integration of Google Translate is particularly relevant, given students' close relationship with technology and their reliance on gadgets. The shadowing technique involves imitation; students listen to pronunciations provided by Google Translate and then replicate them. This study employs a quantitative research approach with a quasi-experimental design. Statistical data analysis is conducted using a paired t-test. The results reveal a paired t-test significance (2-tailed) value of 0.000, which is below the 0.05 threshold. This indicates that the shadowing technique utilizing Google Translate is effective in enhancing students' pronunciation skills. Furthermore, the average score of students in the experimental group increased from 70 on the pre-test to 81 on the post-test. This 11-point improvement signifies that students made substantial advancements in their pronunciation capabilities after being exposed to the shadowing technique with Google Translate.